Comparative study of digestibility of forage legume with sheeps and goats I. In vivo digestibility of cunhã hay - Barros, Nelson Nogueira; Freire, Luiz Carlos Lopes; Lopes, Expedito Aguiar; Johnson, William L. (Pesquisa Agropecuaria Brasileira, 1991)
Six SRD (undefined genotype) goats and six sheep of the Santa Inês genotype, all of them adult males were used to evaluate the nutritive value of the "cunhã" (Clitoria ternatea L.) hay. Goats and sheep were kept in elevated metabolism crates for a 14-day adaptation period, followed by a 7-day collection period of total feces and urine. The forage was offered ad libitum and the animals had free access to water and mineralized salt. Contents of crude protein, neutral detergent fiber and KMnO4 lignin were 22.6%, 49.7% and 8.3%, respectively. There was no significant (P < 0.05) difference between animal species for none of studied parameters. However, when the N balance was evaluated, as a function of the N intake, the result suggest that goats make apparently a better utilization of the dietary N than sheep.